2018
DOI: 10.14361/9783839439135-006
|View full text |Cite
|
Sign up to set email alerts
|

Desi Radio by and for the Panjabi Community: Citizens' Media, Gender, and Participation

Abstract: Desi Radio, the project of the Panjabi Centre located in Southall, West London, was started in 2002 by Ajit Khera and his sister, Amarjit Khera, to promote Panjabi culture, language, and history, and build connection and communication among Panjabi community living in the area. The word, 'Desi', is derived from 'Des' "meaning a specific space, locality or homeland," refers to "Panjab: the Land of the Five Rivers," that sits along the border between India and Pakistan. In the 1947 partition of India, the region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Mitchell and Lewis (Follmer and Badenoch 2018, p. 35) outline that community stations are participatory because they are owned by the community, and thus their voices are articulated by the communities and they are involved in the production of programmes. Haydari's (2018) case study of Desi Radio, a community station in Southall, West London, highlighted that female volunteers found that spending time at the station, producing programmes, and speaking in Punjabi (the presentation is solely in Punjabi) encouraged them to be more conscious of their identities and history: Music and language also play an important role to claim and promote a Panjabi identity beyond the divisions of caste, gender, politics, and religion. The physical location of the radio in the midst of Southall, continuous training activities, and the process of radio production also facilitate connection and communication among all communities.…”
Section: Asian Radio Competitorsmentioning
confidence: 99%
“…Mitchell and Lewis (Follmer and Badenoch 2018, p. 35) outline that community stations are participatory because they are owned by the community, and thus their voices are articulated by the communities and they are involved in the production of programmes. Haydari's (2018) case study of Desi Radio, a community station in Southall, West London, highlighted that female volunteers found that spending time at the station, producing programmes, and speaking in Punjabi (the presentation is solely in Punjabi) encouraged them to be more conscious of their identities and history: Music and language also play an important role to claim and promote a Panjabi identity beyond the divisions of caste, gender, politics, and religion. The physical location of the radio in the midst of Southall, continuous training activities, and the process of radio production also facilitate connection and communication among all communities.…”
Section: Asian Radio Competitorsmentioning
confidence: 99%